Infective endocarditis in dogs in the UK: 77 cases (2009‐2019). (6th November 2022) - Berrezaie, M.; Connolly, D.; Cruzado, J.; Mederska, E.; Dukes‐McEwan, J.; Humm, K.
Abstract : Objectives: To determine the causative organisms, clinical features and outcome of canine infective endocarditis in the UK. Materials and Methods: Medical records of three veterinary referral hospitals were searched for dogs with infective endocarditis between December 2009 and December 2019. Signalment, clinical signs, causative organism, valve affected, treatment and survival data were recorded. Results: Seventy‐seven cases with possible or definite infective endocarditis (according to the modified Duke criteria) were included. The majority were large breed (40/77 – 51.9%). There were 47 of 77 (61%) male dogs and the mean age was 7.3 ±3 years. A causative organism was identified in 26 of 77 (33.8%) cases. The most common organisms were Escherichia coli (7/27 – 25.9%), Pasteurella spp. (5/27 – 18.5%), Staphylococcus spp. (4/27 – 14.8%) and Corynebacterium spp. (4/27 – 14.8%). Bartonella spp. were not detected in any patients. The mitral valve was most commonly affected (48/77 – 62.3%). Clinical features were non‐specific, with lethargy being the most common clinical sign observed (53/77 – 68.8%). Fifty‐three dogs (68.8%) survived to discharge. The median survival time post discharge was 425 days (2 to 3650 days). The development of congestive heart failure was associated with a poorer outcome. Cardiac troponin concentration, antithrombotic use and the development of thromboembolism or arrhythmias were not significantly associated with outcome. Clinical Significance: Some dogs with infective endocarditis that survive to discharge can have a long lifespan. The inability to detect an underlying organism is common and Bartonella spp. may be a less prevalent cause of canine infective endocarditis in the UK than in the USA.